Can the Hydroxyapatite-Coated Skin-Penetrating Abutment for Bone Conduction Hearing Implants Integrate with the Surrounding Skin? - van Hoof, Marc; Wigren, Stina; Duimel, Hans; Savelkoul, Paul H. M.; Flynn, Mark; Stokroos, Robert Jan (Frontiers in Surgery, 2015)
Abstract Introduction Percutaneous implants such as bone conduction hearing implants suffer from complications that include inflammation of the surrounding skin. A sealed skin-abutment interface can prevent the ingress of bacteria, which should reduce the occurrence of peri-abutment dermatitis. It was hypothesized that a hydroxyapatite (HA) coated abutment in conjunction with soft tissue preservation surgery should enable integration with the adjacent skin. Previous research has confirmed that integration is never achieved with as-machined titanium abutments. Here, we investigate, in vivo, if skin integration is achievable in patients using a HA-coated abutment. Materials and Methods One titanium abutment (control) and one HA-coated abutment (case) together with the surrounding skin were surgically retrieved from two patients who had a medical indication for this procedure. Histological sections of the skin were investigated using light microscopy. The abutment was qualitatively analyzed using scanning electron microscopy (SEM). Results The titanium abutment only had a partial and thin layer of attached amorphous biological material. The HA-coated abutment was almost fully covered by a pronounced thick layer of skin components that were organized and composed of different interconnected structural layers. Conclusion Proof-of-principle evidence that the HA-coated abutment can achieve integration with the surrounding skin was presented for the first time.